Ho Chi Minh in using talents - TỐ ANHLÊ; THỊ THU HIỀNNGUYỄN (Tạp chí Nghiên cứu Khoa học Công đoàn, 2017)
Ho Chi Minh really attaches importance to human, treats them as the most precious asset, especially talented one. Therefore, during his revolutionary life, he found every means to uphold, support and promote the human factor, enabled them to bring their abilities to contribute the nation. Thanks to that, he gathered so many talents, those ones who bring faculty to serve country and lead to the great victory to the revolution of Vietnam. The story of Ho Chi Minh with Vo Nguyen Giap, Nguyen Van Huyen, Nguyen Son, Pham Quang Le, Tran HuuTuoc,... is one of the few typical examples to show the proof of the way he use talented person. From that, we could infer the highly valuable experience to use in our work and daily lives. Especially in present conditions, appointing talented person to an important work in Ho Chi Minh thought is more meaningful than ever to bring into full play talent, wisdom and dignity of Vietnamese in service the country, for a rich and powerful Vietnam.